PENEGAKAN HUKUM TERHADAP TINDAK PIDANA KORUPSI DENGAN KERUGIAN NEGARA YANG KECIL DALAM MEWUJUDKAN KEADILAN - Ahmad Muchlis (Fiat Justisia: Jurnal Ilmu Hukum, 2016)
The Circulars letter of deputy attorney of general for special crimes number: B-113/F/ Fd.1/05/2010 can be used as a reference by prosecutors in doing law enforcement against corruption with small losses, but in practice law enforcement, this circular letter is making trouble in practice. The results of this research, namely: the law enforcement against corruption with a small loss of state must pay attention to the values of justice, expediency, and legal certainty. In enforcing the law against corruption with small losses only can be stopped during an investigation by utilizing the exchequer and redress demanded. the reason corruption cases with small losses were still continued by the prosecutor to the court proceedings after enactment of circulator letter because circulator letter contrary to corruption constitution and it has no the strength or binding in legal basis. The Suggestions are addressed for law enforcement officials (police, prosecutor, and judge) in order to do the law enforcement against corruption with small losses in order consider the value of a legal basis, namely: fairness, expediency and certainty. The circular letter of deputy attorney general for special crimes number: B-1113/F/Fd.1/05/2010 in order to be taken as government consideration in formulating the new rules (Ius constituendum). Key words: Corruption, Law Enforcement, Justice